INFLUENCE OF PROMOTION MIX TOWARDS PURCHASE INTENTION IN ANGKASA PHOTO STUDIO - Chandra, William Alden; Aprianingsih, Atik (Journal of Business and Management, 2018)
Abstract. Photography industry has flourished in Indonesia, including photo studio company. However, as one of micro, small and medium enterprises (MSMEs) also face similar problem commonly occur by MSMEs itself, which is the marketing problem. Angkasa Photo Studio is one of the MSME (Small - Medium Enterprise) companies that move in photography sector. Established in 2013 at Bojong Soang 79th street, Bandung, West Java, Angkasa Photo Studio facing a lot of photo studio competitors that is spread in Bandung City. Among marketing mix, promotion is the part of the marketing mix that can be used to raise awareness about the company. Therefore, this research was intended to resolve the promotion mix (advertising, sales promotion, and personal selling) of Angkasa Photo Studio. Moreover, this research also designed in order to identify the influence of the promotional mix toward the purchase intention of Angkasa Photo Studio that could support the photography quality growth / improvement in the future. The data for this research was collected using Quantitative Method approach through offline and online questionnaire to 200 Indonesian respondents. This study adopts the Multiple Linear Regression (MLR) analysis to see the relationship between promotional mix and purchase intention. The result shows that model of promotional mix and purchase intention is significant. Sales promotion is one of promotional mix that significantly and positively impacts purchase intention.Keywords: Promotional Mix, Advertising, Sales Promotion, Personal Selling, Purchase Intention, Angkasa Photo StudioÂ